2011
DOI: 10.1128/jb.06006-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sphingomonas sp. Strain Fr1 PhyR-NepR-σ EcfG Cascade in General Stress Response and Identification of a Negative Regulator of PhyR

Abstract: The general stress response in Alphaproteobacteria was recently described to depend on the alternative sigma factor EcfG , whose activity is regulated by its anti-sigma factor NepR. The response regulator PhyR, in turn, regulates NepR activity in a partner-switching mechanism according to which phosphorylation of PhyR triggers sequestration of NepR by the sigma factor-like effector domain of PhyR. Although genes encoding predicted histidine kinases can often be found associated with phyR, little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(132 citation statements)
references
References 45 publications
5
125
1
1
Order By: Relevance
“…Also in agreement with a role of Paks in the GSR, we were able to delete phyP in the sextuple or septuple kinase mutant backgrounds. Because the PhyR phosphatase PhyP is essential in a WT background preventing lethal hyperphosphorylation of PhyR (10,24), the successful deletion of phyP suggested that a major source of PhyR phosphorylation is absent in these genetic backgrounds. However, because the GSR activity in the sextuple or septuple kinase mutants was still substantially higher than in a phyR mutant ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Also in agreement with a role of Paks in the GSR, we were able to delete phyP in the sextuple or septuple kinase mutant backgrounds. Because the PhyR phosphatase PhyP is essential in a WT background preventing lethal hyperphosphorylation of PhyR (10,24), the successful deletion of phyP suggested that a major source of PhyR phosphorylation is absent in these genetic backgrounds. However, because the GSR activity in the sextuple or septuple kinase mutants was still substantially higher than in a phyR mutant ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify factors positively regulating the PhyR-NepR-σ EcfG cascade, we conducted a genetic screen, performing transposon mutagenesis on a strain expressing the dominant streptomycin-sensitive rpsL1 allele (25) under control of the σ EcfG -dependent ecfG2 promoter (10,24). This construct would allow selection for mutants with an impaired PhyR-NepR-σ EcfG cascade on medium containing streptomycin (details are provided in SI Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations